ANALISIS STRATEGI PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR HONDA DI SAMARINDA - Heriyanto, Eko Budi Setia Mustakim Eddy Soegiarto (EKONOMIA, 2020)
The purpose of this study was to determine the effect of the product on purchasing decisions for Honda motorbikes in Samarinda, The purpose of this study was to determine the effect of Price on purchasing decisions for Honda motorbikes in Samarinda, The purpose of this study was to determine the effect of place / location on the decision to purchase a Honda motorcycle in Samarinda, The purpose of this study was to determine the effect of promotion on the decision to purchase a Honda motorcycle in SamarindaBased on the results of research on the influence of products on the purchase decision of Honda motorcycles in Samarinda by 53.4%, based on the results of research the effect of prices on purchasing decisions of Honda motorcycles in Samarinda amounted to 24.1%, based on the results of the study of the influence of place / location on motorcycle purchasing decisions Honda in Samarinda was 5.6%, based on a study of the effect of promotion on the decision of purchasing Honda motorcycles in Samarinda by 16.63%. Of the total respondents 100 people.